Water Use Characteristics of Weeds: A Global Review, Best Practices, and Future Directions - Singh, Mandeep; Kukal, Meetpal Singh; Irmak, Suat; Jhala, Amit J. (Frontiers in Plant Science, 2022)
Weeds usually penalize crop yields by competing for resources such as water, light, nutrients, and space. Most research in the crop-weed competition domain is limited to assessing crop yield losses due to weed pressure and other crop-weed interactions, overlooking the significant uptake of soil-water by weeds that exacerbates global water constraints and threatens productivity and profitability. The objective of this review was to synthesize globally available quantitative data on weed water use (WU) sourced from 23 peer-reviewed publications (filtered from 233 publications via a multi-step protocol of inclusion criteria) with experimental investigations across space (3 continents), time (1927-2018), weed species (27 broadleaf and 7 grasses) and characteristics, cropping systems (5), soil types (ranging from coarse-textured sand to fine-textured clay soils), determination techniques, experimental factors (environment, management, resource availability, and competition), and aridity regimes (ranging from semi-arid to humid climate). Distributions of weed WU data reported via eight different metrics were assessed for variability and mean WU. A lack of experimental and reporting best-practices in weed WU research was identified that undermined the robustness, transferability, and application of the WU data. Mandatory protocols and best practices typically followed in agricultural water management research were described and recommended for weed scientists to avoid pitfalls in quantifying and presenting weed WU. A model of mixed plant community evapotranspiration was adapted to model weed-crop-soil system evaporation and transpiration in a crop canopy infested with multiple (n) weed species. Finally, potential cross-disciplinary questions across the domains of crop science, weed science, agricultural water management, irrigation science and engineering, and environmental change were proposed to direct and prioritize future research efforts in the crop-weed-water arena.